Separation Axioms in Mixed Fuzzy Topological Spaces - Rashid, MH; Ali, DM (Journal of Bangladesh Academy of Sciences, 2009)
<!--[if gte mso 9]> USER 11.9999 <![endif]--><!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> We deal with fuzzy topology. In this paper, we introduce the concept of mixed fuzzy topology which is constructed from two fuzzy topologies on the same fuzzy set X and study several features of this mixed fuzzy topology. Keywords: Fuzzy Topological Spaces, Mixed fuzzy topology doi: 10.3329/jbas.v32i2.2433 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 142-150